2017
DOI: 10.1590/s0102-865020170100000002
|View full text |Cite
|
Sign up to set email alerts
|

Numeric and volumetric changes in Leydig cells during aging of rats

Abstract: Purpose: To analyze the effects of aging in rats on the nuclear volume, cytoplasmic volume, and total volume of Leydig cells, as well as their number. Methods: Seventy-two Wistar rats were divided into six subgroups of 12 rats, which underwent right orchiectomy at 3, 6, 9, 12, 18, and 24 months of age. The weight and volume of the resected testicles were assessed. A stereological study of Leydig cells was conducted, which included measurements of cell number and nuclear, cytoplasmic, and total cell volumes. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
(27 reference statements)
0
2
0
1
Order By: Relevance
“…However, Ichihara et al (22) observed that the number of Leydig cells in paired testes doubled with age, although the average volume of those cells decreased. In rat, a reduction of the total cell volume of Leydig cells accompanied by the deficient ability to produce testosterone in response to LH was reported but no changes in the total number of these cells during aging were observed (23,24).…”
Section: Aging and Testicular Morphologymentioning
confidence: 99%
“…However, Ichihara et al (22) observed that the number of Leydig cells in paired testes doubled with age, although the average volume of those cells decreased. In rat, a reduction of the total cell volume of Leydig cells accompanied by the deficient ability to produce testosterone in response to LH was reported but no changes in the total number of these cells during aging were observed (23,24).…”
Section: Aging and Testicular Morphologymentioning
confidence: 99%
“…Leydig cells are present in the testis interstitium, and synthesize androgens via steroidogenesis [ 58 ]. Therefore, shrinkage of the nucleus will ultimately affect the Leydig cell’s steroidogenic capacity and subsequently lead to disruption of spermatogenesis [ 58 - 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A hiperplasia das células de Leydig tem sido observada em camundongos com "feminização" testicular, isto é, baixa influência de testosterona, e àqueles associados ao tratamento com estrógenos ou inibidores da 5-α-redutaseTrindade et al 2013).Ademais observamos que não houve diferença significativa entre o número de células de Leydig por testículo nos animais senis quando comparados aos níveis dos jovens. Similarmente,Neves et al (2017) ao estudar a influência do envelhecimento masculino sob a estereologia das células de Leydig, notou que a quantidade de células de Leydig por testículo não variou entre os camundongos jovens e senis, assim como estudos realizados por Wang et al (2012) e Chen et al (1994). Adicionalmente, Chen et al (2009) e Koeva et al (2009) observaram que durante o envelhecimento as células de Leydig desenvolvem problemas nas vias esteroidogênica, resultando na redução da produção hormonal.…”
unclassified